Feasibility of endoscopic submucosal dissection of lesions at anastomosis site post-colorectal surgery: a case series - Krutsri, Chonlada; Toyonaga, Takashi; Ishida, Tsukasa; Hoshi, Namiko; Baba, Shinichi; Miyajima, Nelson Tomio; Kodama, Yuzo (Endoscopy International Open, 2019)
Background and study aims Patients who have undergone colorectal surgery for resection of cancer and benign lesions are at risk for recurrent, residual, or metachronous lesions at the anastomosis site. Surgical resection of such lesions is difficult because of adhesions, and a stoma may be required as there are risks for leakage after resection. The feasibility and safety of endoscopic submucosal dissection (ESD) for these lesions remain unknown. Therefore, this case series aimed to examine the feasibility and safety of ESD by evaluating the clinical outcomes.Patients and methods We retrospectively investigated five patients who underwent ESD by a single expert for superficial neoplastic lesions at the anastomosis site after previous colorectal surgery.Results R0 resections were achieved for all lesions. Mean procedure time was 160.6 minutes. Mean dimensions of the resected specimen and tumor were 52.4 mm and 31.8mm, respectively. None of the patients had complications or recurrence after surveillance colonoscopy 1-year post-resection.Conclusions In an expert’s hands, ESD at the anastomosis site might be feasible minimally invasive treatment for superficial neoplastic lesions.